The Relationship Between Dietary Diversity Among Women of Reproductive Age and Agricultural Diversity in Rural Tanzania. Issue 1 (March 2020) - Bellows, Alexandra L.; Canavan, Chelsey R.; Blakstad, Mia M.; Mosha, Dominic; Noor, Ramadhani A.; Webb, Patrick; Kinabo, Joyce; Masanja, Honorati; Fawzi, Wafaie W.
Background: Agriculture can influence diets through consumption of home-produced foods or increased purchasing power derived from sale of agricultural commodities. Objective: This article explores cross-sectional relationships between agricultural diversification and dietary diversity (a proxy for micronutrient adequacy) among women of reproductive age in rural Tanzania. Methods: Dietary diversity was measured using the women's minimum dietary diversity score indicator. Data were analyzed from the baseline survey of a cluster randomized control trial in Rufiji, Tanzania. One woman of reproductive age was randomly surveyed from each eligible household, totaling 1006 individuals. Generalized linear mixed-effects models were used to estimate the relationship between agricultural indicators and dietary diversity. Results: Median dietary diversity score for women was 3.00 (interquartile range: 2-3). Approximately 73% of households grew at least 1 crop in the previous year. Women's dietary diversity score was positively associated with cropping diversity ( P for trend = .04), ownership of livestock (adjusted coefficient: 0.30; 95% confidence interval [CI]: 0.08-0.44; P = .005), cash crop production (adjusted coefficient: 0.22; 95% CI: 0.03-0.41; P = .02), and production of pulses (adjusted coefficient: 0.50; 95% CI: 0.27-0.74; P < .0001) and other vegetables (adjusted coefficient: 0.64; 95% CI: 0.11-1.17; P = .02). Conclusions: Average dietary diversity is well below the recommended 5 food groups per day, a widely used indicator of micronutrient adequacy. Since the majority of households participate in agriculture, the efforts to promote agricultural diversification and/or specialization and sale of agricultural goods may positively influence dietary diversity and associated health and nutrition outcomes.